Five‐year trend in healthcare access and patient‐reported health outcomes among women veterans. Issue 2 (14th November 2019) - Vance, Billie; Alhussain, Khalid; Sambamoorthi, Usha
Abstract: Background: This study aimed to describe the five‐year trend in healthcare access, health‐related quality of life (HRQoL), and health outcomes in women Veterans. Methods: A retrospective, pooled, cross‐sectional study design was employed. Five‐year trend was assessed using 2013 and 2017 Behavioral Risk Factor Surveillance System (BRFSS) data. Bivariate, multivariable logistic regression, and ordinary least squares regression analyses were conducted. Results: A total of 6561 women Veterans, aged 18 to 64 years (3534 in 2013 and 3027 in 2017) were included. Compared to 2013, more women Veterans in 2017 reported increased healthcare insurance and decreased cost as a barrier to care. Women Veterans with health insurance were less likely to report cost as a barrier to care. There were no statistically significant differences in HRQoL in bivariate or ordinary least squares regression analyses between BRFSS years. Conclusion: Federal policy and Veterans Health Administration expansion have had an impact on improving healthcare access to women Veterans. However, increased healthcare access alone does not translate into improved HRQoL or health outcomes for women Veterans. Future policies should not only focus on increasing healthcare access, but also improving health outcomes, especially HRQoL. The quality of the healthcare accessed must be a focus for future research and policy.